PENGARUH DEBT RATIO TERHADAP RETURN ON EQUITY STUDI PADA PT. KARYA LESTARI MANDIRI GARUT - sungkowo, wulandari; Apriliyani, Gita Rosita (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2026)
This study aims to determine how the Debt Ratio (DR) is related to or affects Return on Equity (ROE). The data used is secondary data obtained from financial reports for the period 2014-2019. The analysis method used was ratio measurement, consisting of the Debt Ratio using the Debt Ratio formula, Return on Equity using the Return on Equity formula, simple correlation analysis, and simple regression analysis of the coefficient of determination using the SPSS program. The results showed that during the 2014-2018 period, the Debt Ratio and Return on Equity fluctuated. The test conducted using simple linear regression analysis produced the regression equation Y=-2.496+0.432X, which means that every 1 increase in Debt Ratio will affect an increase in Return On Equity of 0.432, and if Debt Ratio = 0, the value of Return On Equity is -2.429. And from the results of the coefficient of determination analysis, an R-Square value of 0.233 was obtained, which means that the effect of the Debt Ratio on Return on Equity is 23.33%, while the remaining 76.67% is influenced by other factors that were not examined.